English Speaking Anxiety Among Trainee Teachers in the Institute of Teacher Education Tengku Ampuan Afzan (Current Research in Education: Conference Series Journal, 2024)
This study aims to uncover the causes of English speaking anxiety of trainee teachers at the Institute of Teacher Education Tengku Ampuan Afzan, Kuala Lipis, Pahang and propose strategies to reduce the causes of anxiety. One of important aspects that influences speaking skills is psychological factors, namely beliefs, feelings, and behaviors. To collect in-depth data, this study included semi-structured interviews with seven trainee teachers enrolled in English for Young Learners lessons from June to August, observations, and document analysis. Documents were observed and analyzed to support conclusions from the interviews, which were transcribed verbatim to reveal four themes: (i) physiological and psychological changes, (ii) having a restricted English vocabulary, (iii) grammatical and pronunciation issues, and (iv) lack of self-confidence. The finding suggested that the psychological element of trainee teachers’ concerns about English speaking skills at the Institute of Teacher Education Tengku Ampuan Afzan in the field of Early Childhood Education should be properly addressed. Improving trainee teachers’ English speaking skills can have a significant impact on preschool children’s knowledge of the learning strands of language and communication particularly in the English.